2017
DOI: 10.1111/jgs.14846
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Geriatric Assessment for Prevention of Delirium After Hip Fracture: A Systematic Review of Randomized Controlled Trials

Abstract: There was a reduction in the incidence of delirium after hip fracture with CGA. This is in keeping with results of non-randomized controlled trials and trials in other populations. Team-based interventions appeared superior in contrast to the Ellis CGA paper, but it is likely that heterogeneity in interventions and population studied affected this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 26 publications
(100 reference statements)
2
36
1
Order By: Relevance
“…Moreover, orthogeriatrician-led perioperative care has led to a notable reduction in morbidity and mortality amongst hip fracture patients. In our study, we found a much lower incidence of delirium than that found in previous studies [ 10 12 ]. This finding may in part be explained by the aforementioned improvements in care but there are several other possible explanations including variations in definition of delirium and diagnostic accuracy.…”
Section: Discussioncontrasting
confidence: 73%
“…Moreover, orthogeriatrician-led perioperative care has led to a notable reduction in morbidity and mortality amongst hip fracture patients. In our study, we found a much lower incidence of delirium than that found in previous studies [ 10 12 ]. This finding may in part be explained by the aforementioned improvements in care but there are several other possible explanations including variations in definition of delirium and diagnostic accuracy.…”
Section: Discussioncontrasting
confidence: 73%
“…21,22 Similar to previous reports, we also identified functional impairment on admission and living in nursing homes as risk factors for developing new episodes of delirium in HF patients. 21,22 Similar to previous reports, we also identified functional impairment on admission and living in nursing homes as risk factors for developing new episodes of delirium in HF patients.…”
Section: Discussionsupporting
confidence: 87%
“…The exhaustive assessment of delirium carried out in the orthogeriatric service, the high prevalence of dementia and the high number of patients coming from nursing homes all might have contributed to the high incidence of delirium registered in our cohort, but nevertheless they are in line with other studies. 21,22 Similar to previous reports, we also identified functional impairment on admission and living in nursing homes as risk factors for developing new episodes of delirium in HF patients. 3 In Figure 1 Risk factors for delirium according to the multivariate logistic regression analysis.…”
Section: Discussionsupporting
confidence: 87%
“…44 The CGA is used to determine the medical, psychological, and functional capabilities of elderly patients in order to develop an integrated plan for treatment and prevention of delirium. 42,45 Lundström et al found that in 199 geriatric hip fracture patients, CGA intervention reduced both the number of postoperative complications and length of total hospitalization by 10 days compared to those without intervention. 27 Thus, provider foreknowledge of delirium risk factors outlined in this study may help multidisciplinary teams develop integrated plans and policies for the prevention of delirium and reduce costs to patients, Medicare, and hospital systems going forward.…”
Section: Discussionmentioning
confidence: 99%